2021
DOI: 10.1155/2021/5854056
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis on the Clinical Effect of High‐Dose Glucocorticoids Combined with Immunosuppressants on Patients with Myasthenia Gravis Undergoing Video‐Assisted Thoracoscopic Surgery

Abstract: Objective. The purpose of the study was to investigate the clinical effect of high-dose glucocorticoids (GCS) combined with immunosuppressants on the treatment of myasthenia gravis (MG) with video-assisted thoracoscopic surgery (VATS). Methods. A total of 106 MG patients admitted to the neurology department of our hospital from February 2016 to February 2020 were selected as the study subjects and divided into experimental group ( n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%